Supersonic Shear Wave Imaging to Assess Arterial Nonlinear Behavior and Anisotropy: Proof of Principle via Ex Vivo Testing of the Horse Aorta. (22nd September 2014) - Shcherbakova, D. A.; Papadacci, C.; Swillens, A.; Caenen, A.; De Bock, S.; Saey, V.; Chiers, K.; Tanter, M.; Greenwald, S. E.; Pernot, M.; Segers, P.
Abstract : Supersonic shear wave imaging (SSI) is a noninvasive, ultrasound-based technique to quantify the mechanical properties of bulk tissues by measuring the propagation speed of shear waves (SW) induced in the tissue with an ultrasound transducer. The technique has been successfully validated in liver and breast (tumor) diagnostics and is potentially useful for the assessment of the stiffness of arteries. However, SW propagation in arteries is subjected to different wave phenomena potentially affecting the measurement accuracy. Therefore, we assessed SSI in a less complex ex vivo setup, that is, a thick-walled and rectangular slab of an excised equine aorta. Dynamic uniaxial mechanical testing was performed during the SSI measurements, to dispose of a reference material assessment. An ultrasound probe was fixed in an angle position controller with respect to the tissue to investigate the effect of arterial anisotropy on SSI results. Results indicated that SSI was able to pick up stretch-induced stiffening of the aorta. SW velocities were significantly higher along the specimen's circumferential direction than in the axial direction, consistent with the circumferential orientation of collagen fibers. Hence, we established a first step in studying SW propagation in anisotropic tissues to gain more insight into the feasibility of SSI-based measurements in arteries.